2005
DOI: 10.1007/s10495-005-1880-5
|View full text |Cite
|
Sign up to set email alerts
|

Disease-associated fibronectin matrix fragments trigger anoikis of human primary ligament cells: p53 and c-myc are suppressed

Abstract: Inflammation in periodontal disease is characterized by the breakdown of the extracellular matrix. This study shows that an inflammation-associated matrix breakdown fragment of fibronectin (FN) induces anoikis of human periodontal ligament (PDL) cells. This 40 kDa fragment was identified in human inflammatory crevicular fluid and is associated with disease status. Previously, we reported that a similar recombinant FN fragment triggered apoptosis of PDL cells by an alternate apoptotic signaling pathway that req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 19 publications
(23 reference statements)
1
34
0
Order By: Relevance
“…This breakdown product of fibronectin originates from the proteolytic cleavage of intact fibronectin, and it is found in the gingival crevicular fluid of patients affected by periodontal disease and in joint fluids from arthritic patients (29,33). Our earlier studies showed that this proteolytic fragment and its recombinant counterpart, AFn, trigger aberrant cell signaling in primary cells that ultimately leads to apoptosis (13,40,68). In addition, the breakdown products of macromolecules generate nitric oxide in cells present in inflamed sites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This breakdown product of fibronectin originates from the proteolytic cleavage of intact fibronectin, and it is found in the gingival crevicular fluid of patients affected by periodontal disease and in joint fluids from arthritic patients (29,33). Our earlier studies showed that this proteolytic fragment and its recombinant counterpart, AFn, trigger aberrant cell signaling in primary cells that ultimately leads to apoptosis (13,40,68). In addition, the breakdown products of macromolecules generate nitric oxide in cells present in inflamed sites.…”
Section: Discussionmentioning
confidence: 99%
“…We previously identified a recombinant altered fibronectin molecule and a comparable disease-associated proteolytic fibronectin fragment that induce apoptosis in primary cells, including PDL cells (13,68). This apoptotic process is unique since it is accompanied by a downregulation of p53 at both the transcriptional and the posttranslational level.…”
mentioning
confidence: 99%
“…32 The V Ć¾ Hƀ fragment is comparable to the 40 kDa naturally occurring proteolytic fragment found in diseased patient fluids. 33,34 Both fragments rely on interactions with the heparin-binding domain and V region of FN.…”
Section: Methodsmentioning
confidence: 99%
“…6A-C). Certain fibronectin fragments can promote inflammation (Barilla and Carsons, 2000;Norris et al, 1982), whereas other fibronectin fragments are known to regulate cell migration, growth and survival (Clark et al, 1988;Dai et al, 2005;Homandberg et al, 1985). Therefore, tight regulation of ECM fibronectin degradation and endocytosis provides a mechanism for limiting the accumulation of bioactive matrix fragments.…”
Section: Mt1-mmp Regulates Fibronectin Turnover 4045mentioning
confidence: 99%